CUSTOMER SATISFACTION LEVEL ANALYSIS OF QUALITY ANIMAL CLINIC SERVICES IN SURABAYA (CLINIC X SURABAYA) - Enny Istanti; Ruchan Sanusi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
There is a phenomenon of people in big cities, especially Surabaya, who love and maintain pavilions and cats.The purposes of this study are [1] to determine and analyze the level of customer satisfaction with the service quality of veterinary clinics, [2] to determine and analyze improvement strategies in implementing customer satisfaction levels on the quality of veterinary services. This study uses a qualitative approach. sampling based on accidental sampling technique (accidental sampling). The results of this study are CSI below 100% means that customers are not satisfied and IR above 1.00 means that it can be maintained or major improvement efforts. And the improvement strategy used is that doctors are expected to have extra responsiveness in dealing with and dealing with patients who come. So that pets that are brought to the clinic for treatment do not die and give a great sense of satisfaction.